Toward Content-Aware Video Partitioning Methods for Distributed HEVC Video Encoding - Myunghoon Jeon; Byoung-Dai Lee (Institute of Advanced Engineering and Science, 2015)
Recently, cloud computing has emerged as a potential platform for distributed video encoding due to its advantages in terms of costs as well as performance. For distributed video encoding, the input video must be partitioned into several segments, each of which is processed over distributed resources. This paper describes the effect of different video partitioning schemes on overall encoding performance in the distributed encoding of High-Efficiency Video Coding (HEVC). In addition, we explored performances of video partitioning schemes on the basis of the types of the content to be encoded